Analysis of the Implementation of Regional Government Credit Cards (KKPD) in Tangerang City - Ni Made Sri Wardani; Faris Windiarti; Maulida Salmi Utie (Universitas Negeri Padang, 2026)
Purpose – This research analyzes the implementation of Regional Government Credit Cards (Kartu Kredit Pemerintah Daerah or KKPD) for revolving fund (uang persediaan) management in Tangerang City. The study aims to evaluate the extent to which KKPD enhances the effectiveness of local financial management. Design/methodology/approach – Employing a qualitative case study approach, data were collected from ten local government agencies under Tangerang City through interviews, observations, and document analysis. Findings – Findings indicate that the use of KKPD remains relatively low. Most of activities still used the cash on hand for practical payment mechanism. These findings were due to the limited supporting infrastructure within the governmental procurement platform which allows for the use of KKPD. Originality/value – This research used the UTAUT dimensions to analyze the implementation of KKPD in public sector institutions. Research limitations/implications – The generalizability of this study for other local government in Indonesia should be taken very carefully considering the differences in local government characteristics. Article Type: Research paper